An Insight into Preparatory Methods and Characterization of Orodispersible Film-A Review - Ahmad Salawi (MDPI AG, 2022)
Over the past few decades, researchers and companies have been trying to develop novel drug delivery systems to ensure safety, efficacy, compliance, and patient acceptability. Nowadays drug discovery and development are expensive, complex, and time-consuming processes, but trends are moving toward novel drug delivery systems. This delivery system helps to achieve drug response by local and systemic action through different routes. This novel approach of preparing orodispersible films (ODFs) provides benefits to paediatric, geriatric, and bedridden patients. This review paper aims to provide details on the preparation, characterization, and evaluation of ODFs; it also aims to focus on the positive and negative factors that affect film formulation and give an insight into potential drug candidates and polymers for use in ODFs. ODFs are effective, safe, and have good bioavailability as compared to fast-disintegrating tablets. The novel approach has various advantages because it provides instant effects in emergency situations and in schizophrenic and dysphasic patients without the need for taking water, the films disintegrating within a few seconds in the oral cavity. The solvent casting method is the most frequently used technique to develop ODFs, using film-forming polymers, which have a fast disintegration time, improved drug dissolution, and better drug contents.